Studies in earth sciences: a volume in honour of William Dixon West - West, William Dixon; Murty, T. V. V. G. R. K.; Rao, S. S. (Suryadevara Subba), 1936- (Today and Tomorrow's Printers and Publishers, 1971)
Festschrift in honour of William Dixon West, 1901- former Director of the Geological Survey of India.